Numeracy and learning difficulties : approaches to teaching and assessment - Westwood, Peter S. 1936- (Australian Council for Educational Research Press, 2000)
This book is about: Developing numeracy: current issues in learning and teaching; More on children's learning; Improving numeracy: general teaching principles and practices; Teaching basic number skills; Teaching problem-solving skills and strategies; Assessment; and Recommended resources.